2017
DOI: 10.1136/gutjnl-2016-313425
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and pharmacological treatment of abdominal pain in IBS

Abstract: This review introduces the principles of visceral sensation and appraises the current approaches to management of visceral pain in functional GI diseases, principally IBS. These approaches include dietary measures including fibre supplementation, low fermentable oligosaccharides, disaccharides, monosaccharides and polyols diet, and pharmacological approaches such as antispasmodics, peppermint oil, antidepressants (tricyclic agents, selective serotonin reuptake inhibitors), 5-HT receptor antagonists (alosetron,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
123
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 107 publications
1
123
0
6
Order By: Relevance
“…For research animals, provision of analgesia is an obligation that is becoming better recognized and acknowledged as an approachable challenge that need not affect outcome in models involving intestinal pain, as in the IBD models studied here, or elsewhere . Optimal treatment in animals can aid the translation to human medicine, where the challenge of intestinal pain is frequently met with opioids for non‐inflammatory (irritable bowel syndrome; IBS) or inflammatory (IBD) conditions …”
Section: Discussionmentioning
confidence: 99%
“…For research animals, provision of analgesia is an obligation that is becoming better recognized and acknowledged as an approachable challenge that need not affect outcome in models involving intestinal pain, as in the IBD models studied here, or elsewhere . Optimal treatment in animals can aid the translation to human medicine, where the challenge of intestinal pain is frequently met with opioids for non‐inflammatory (irritable bowel syndrome; IBS) or inflammatory (IBD) conditions …”
Section: Discussionmentioning
confidence: 99%
“…More recently, anticonvulsants, predominately gabapentin and pregabalin, have been used to treat visceral pain [56]. Recent studies of gabapentin and pregabalin have shown beneficial effects on visceral hypersensitivity [57, 58].…”
Section: Management Of Pain In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…It is unknown whether NGF plays a major role in the rodent model of FD and whether the possible GES effects on gastric hypersensitivity might be mediated via the NGF mechanism. Opioids, such as μ‐opioid receptor (OR), κ‐OR agonist, and δ‐OR antagonist (eluxadoline), have been used to treat pain, including visceral pain in gastrointestinal functional disorders, such as irritable bowel syndrome . We were also interested in possible analgesic effects of GES on opioid mechanisms.…”
Section: Introductionmentioning
confidence: 99%